2007
DOI: 10.1002/mus.20815
|View full text |Cite
|
Sign up to set email alerts
|

Effects of aging on contact heat‐evoked potentials: The physiological assessment of thermal perception

Abstract: Age significantly influences the detection thresholds to noxious heat; such thresholds depend on responses in the cerebral cortex to thermal stimuli and the psychophysical perception of such responses. To understand the influence of age on cerebral responses, we used contact heat-evoked potentials (CHEPs) to investigate the physiology of cerebral responses to thermal stimuli in 70 healthy subjects (33 men and 37 women, 39.56 +/- 12.12 years of age). With heat stimulation of fixed intensity (51 degrees C) on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

14
44
0
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(60 citation statements)
references
References 41 publications
14
44
0
2
Order By: Relevance
“…Several groups have established CHEPS as a clinically feasible approach to examine the physiology of thermonociceptive nerves. [15][16][17][18][19][20][21] CHEPS, by activating Ad fibers, can be recorded at the vertex of the skull for clinical use.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several groups have established CHEPS as a clinically feasible approach to examine the physiology of thermonociceptive nerves. [15][16][17][18][19][20][21] CHEPS, by activating Ad fibers, can be recorded at the vertex of the skull for clinical use.…”
Section: Introductionmentioning
confidence: 99%
“…CHEPS can record a N-P waveform mediated by Ad fibers in normal subjects by applying a suprathreshold and fixedintensity thermal stimulus. 20,21 This test records the brain response to heat pain conveyed by thermonociceptive nerves and can detect dysfunctions due to small-diameter sensory nerve degeneration. Several studies have shown reduced CHEPS amplitudes and prolonged latencies in patients with skin denervation and sensory neuropathy of different causes.…”
mentioning
confidence: 99%
“…380 -500 ms (u.a. Chen et al 2006, Greffrath et al 2007, Roberts et al 2008 (Chao et al 2007, Greffrath et al 2007, Roberts et al 2008, Warbrick et al 2009 Habituationsprozesse zurückzuführen ist (Greffrath et al 2007, Warbrick et al 2009 Harkins et al 1989, Raselli & Broderick 2007, Schmidt et al 2011, Wade et al 1992). …”
Section: 1somatosensorik Und Schmerzunclassified
“…Verschiedene Autoren konnten einen positiven Zusammenhang zwischen den Amplituden und den subjektiven Intensitätseinschätzungen nach schmerzhaften Kontakthitzereizen nachweisen (Chao et al 2007, Moont et al 2011, Roberts et al 2008 (Chao et al 2007, Moont et al 2011, Roberts et al 2008 (Brown & Jones 2010, Brown et al 2008, Moont et al 2011). …”
Section: Form Der Evozierten Potentiale Und Bewertung Der Reizeunclassified
“…Recent studies indicate that aging interferes with the nociceptive threshold. 10 In addition, the initial negative latency correlates with sex, with shorter latencies noted in female patients.…”
mentioning
confidence: 99%